Dynamic linkages between housing and lot prices: Empirical evidence from Helsinki - Elias Oikarinen (Aboa Centre for Economics (ACE), 2009)
The price of vacant land zoned for housing is expected to be tightly linked to housing prices. In informationally efficient markets, vacant lot price movements should not lag changes in housing prices. In practice, however, the leading role of housing appreciation with respect to vacant lot price growth may be caused by factors such as thin trading and lack of publicly available data on transactions in the lot market. Based on a vector error-correction model employing quarterly data from the Helsinki Metropolitan Area over 1988Q1-2008Q2, this study shows that housing price movements lead price changes in the market for vacant lots and housing prices react to shocks in the demand side fundamentals more rapidly than lot prices. Overall, the empirical results give support to the hypothesis that house prices respond to shocks influencing the value of developed land first, after which the price level of vacant lots reacts to the information revealed by housing prices. Hence, the results indicate that the market for lots is more informationally inefficient than the housing market. Furthermore, the empirical findings suggest that construction costs too react to income and interest rate shocks.
Keywords: R31; R32; E31; 330; Housing; land; lot prices; dynamics; construction costs